The Effect of Fraud Hexagon Model on Fraud Financial Statements in Companies in the Financial Sector - Nuril Janah; Lia Rachmawati; Nanda Widaninggar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to find the effect of the Fraud Hexagon Model on the Financial Statement Fraud. Fraud Hexagon Model consists of Stimulus which is proxied by Financial Target and External Pressure, Opportunity is proxied by Ineffective Monitoring, Rationalization is proxied by External Quality Auditor, Capability is proxied by Change in Director, Ego is proxied by Frequent Number of CEO's Picture, and Collusion proxied by Political Connection. This study uses purposive sampling method, and the number of companies that are sampled in the study are 42 of 105 companies and analyzed by binary logistic regression analysis. The results of this study found that External Pressure, Auditor External Quality, and Frequent Number of CEO's Picture have an effect on Financial Statement Fraud. Meanwhile, Financial Target, Ineffective Monitoring, Change in Director, and Political Connection have no effect on Financial Statement Fraud on companies in the financial sector listed on the IDX in 2016-2020.